Continuity and Change in Labour Relations: Facing Facts - Goldenberg, H. Carl (Relations industrielles / Industrial Relations, 1978)
Continuity implies the existence of certain basic facts which must be faced when we think in terms of change because change in the area of labour-management relations cannot be effected in a vacuum. And the basic fact is that labour-management relations are human relations, that basic to the conduct of labour relations and the avoidance of industrial disputes is an appreciation of underlying human fact ors.